2013
DOI: 10.17221/7083-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A review on Schmallenberg virus infection: a newly emerging disease of cattle, sheep and goats

Abstract: Schmallenberg virus (SBV) infection is an emerging infectious disease of ruminants first described in Germany in November, 2011. Since then it has spread very rapidly to several European countries. The disease is characterised by fever, reduced milk production and diarrhoea in cattle and abortions, stillbirths and foetal abnormalities in sheep and goats. SBV is an enveloped, negative-sense, segmented, single-stranded RNA virus, classified in the genus Orthobunyavirus of the Bunyaviridae family, and is closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
7
0
8
Order By: Relevance
“…Furthermore, some authors reported that these viruses could cause arthrogryposis, hydranencephaly, microcephaly and cerebellar hypoplasia defects (Givens and Marley 2008, Brachthäuser et al 2012, Pawaiya and Gupta 2013. Based on anamnesis at the same grazing region, there was no malformation case seen either in the herd that the case was observed or in the other closer herds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors reported that these viruses could cause arthrogryposis, hydranencephaly, microcephaly and cerebellar hypoplasia defects (Givens and Marley 2008, Brachthäuser et al 2012, Pawaiya and Gupta 2013. Based on anamnesis at the same grazing region, there was no malformation case seen either in the herd that the case was observed or in the other closer herds.…”
Section: Discussionmentioning
confidence: 99%
“…Schmallenberg virüsün nakli; nehir, şelale ve göl kenarlarında çok sayıda bulunan kan emici sineklerle (özel-likle Culicoides spp) gerçekleşmektedir (8,18). Bu çalış-mada; pozitiflik belirlenen dört hayvanın bulunduğu sürü-lerin ikisinin, şüpheli olarak belirlenen altı hayvanın bulunduğu sürülerin üçünün büyük su kaynaklarına yakın olmamasından dolayı, hastalığın görülmesinde su kaynaklarının varlığının tek başına etkili olamayacağı düşünül-müştür.…”
Section: Tartışma Ve Sonuçunclassified
“…Hastalık; sığırlarda ateş, iştahsızlık, süt üretiminde azalma, kondüsyon kaybı ve ishalle karakterizeyken (11,14,18), koyun ve keçilerde kongenital malformasyonlarla beraber abortus ve ölü doğum gözlenmektedir (18). Kuzu, oğlak ve buzağılarda transplasental enfeksiyonlarla; artrogripozise, columna vertabralis (kifoz, lordosis, skolyoz, tortikolis) ve kafatası (makrosefali, brachygnathia inferior) bozuklukları gibi şiddetli kongenital malformasyonlara, çeşitli beyin (hidranensefali, porensefali, serebellar hipoplazi, beyin kökü hipoplazisi) ve spinal cord hasarlarına neden olabilmektedir (6,7).…”
Section: Introductionunclassified
See 2 more Smart Citations